2015
DOI: 10.1155/2015/518167
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Plasmid-Mediated Quinolone Resistance Determinants and OqxAB Efflux Pumps among Extended-Spectrumβ-Lactamase ProducingKlebsiella pneumoniaeIsolated from Patients with Nosocomial Urinary Tract Infection in Tehran, Iran

Abstract: Objective. Plasmid-mediated quinolone resistance (PMQR) plays an important role in the development of clinical resistance to quinolone. The aim of this study was to investigate PMQR determinants among extended-spectrum β-lactamases- (ESBL-) producing Klebsiella pneumoniae recovered from patients with nosocomial urinary tract infection (UTI). Methods. A total of 247 ESBL-producing K. pneumoniae isolates were collected from 750 patients with UTI. ESBL production was confirmed by double disc synergy test and comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
(42 reference statements)
8
17
2
Order By: Relevance
“…A substantially higher proportion of qepA and aac-(6 ′) -Ib was found among PMQR genes. This trend is in agreement with recent clinical surveillance results showing significantly higher occurrence of aac-(6 ′) -Ib-cr 56575859. Although no comprehensive comparison of PMQR levels in aquatic environments could be found in the literature, two recent investigations on bacteria isolated from aquatic environments suggested the occurrence of aac-(6 ′) -Ib-cr is indeed higher than qnr and qepA genes6061.…”
Section: Discussionsupporting
confidence: 90%
“…A substantially higher proportion of qepA and aac-(6 ′) -Ib was found among PMQR genes. This trend is in agreement with recent clinical surveillance results showing significantly higher occurrence of aac-(6 ′) -Ib-cr 56575859. Although no comprehensive comparison of PMQR levels in aquatic environments could be found in the literature, two recent investigations on bacteria isolated from aquatic environments suggested the occurrence of aac-(6 ′) -Ib-cr is indeed higher than qnr and qepA genes6061.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, a study conducted in Iran has reported that almost all ESBL-producing strains were resistant to these antibiotics (23). Based on the findings, in the present study, the resistance of the ESBL-producing strains against aminoglycosides (68.3%) was higher than those reported by Goudarzi et al (46.35%), Shams et al (45%), and Eftekhar (36.7%) (10,13,22). Moreover, more than 50% of the ESBLproducing K. pneumonia isolates were resistant against fluoroquinolones, and the highest and lowest resistance was, respectively, found against nalidixic acid (65.4%) and gatifloxacin (40.4%).…”
Section: Discussionsupporting
confidence: 54%
“…However, PMQR determinants were found in 80.76% of ESBLproducing isolates. Based on the studies conducted in Iran, the prevalence of PMQR genes in K. pneumonia isolates ranges from 39.5 to 89.1% (10,13,26,27,29,30), while in other countries it ranges from 11.1 to 100% (e.g., South Korea, the United States, and Syria) (31)(32)(33). Generally, susceptibility to quinolones and aminoglycosides is lower in species harboring the acetyltransferase aac(6')-Ib-cr gene.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] In the present study, the prevalence of oqxAB gene (6.3%) was very low as compared with previous reports. 23,29,31 Thus, indicating that it may not be a major mediator of fluoroquinolone resistance. qepA gene was not detected in the present study and similar findings has been documented from Thailand and Iran.…”
Section: Discussionmentioning
confidence: 99%